SUSTAINABLE ISLAMIC DA'WAH A PANACEA FOR A SYNCRETIC PRACTICES OF EGGON ERRO MUSLIMS - Muhammad Maga Sule; Muhammad Abdullahi Maigari; Yahaya Sulaiman (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
This paper is a contribution and a piece of Da’wah work towards eradicating syncretic practice and the worship ancestors (Likya) among Eggon Erro people in Eggonland. The study revealed that religious syncretism is common among many Eggon Erro Muslims, but its main contention was that it had a negative influence on a lot of them. If continual awareness and Da'wah could be carried out, the problem will be eradicated. This study was conducted using a survey method, and data were collected through in-depth interviews. The results of this study showed the need for a sustainable Da'wah to combat the issue of syncretism that many Eggon Erro Muslims are into, and their persistent indulgence in syncretic practices and its effects on their faith (Iman). While acknowledging the efforts of some Muslim scholars to end this endemic problem, this study reveals that Tauheed is not well inculcated into the minds of many Eggon Erro Muslims yet. Therefore, for the purpose of effectively instilling practical Tauheed in their minds, a concerted effort is required among all stakeholders in the task of spreading Islamic education in the communities of the Eggon Erro. The paper concluded that educating the youthful population and the elderly through Islamic education would go a long way to eradicate this menace.